Interactive immersive virtual reality to enhance students' visualisation of complex molecules - Won, Mihye; Mocerino, Mauro; Tang, Kok-Sing; Treagust, David; Tasker, Roy (Springer, 2019)
Computer-aided visualisation has played an essential role in helping students construct a better understanding of molecular interactions over the years but it has limitations in supporting 3D visualisation, especially for complex molecules. As an alternative platform, immersive virtual reality (VR) holds great promise for addressing students' difficulties. This paper examines the educational possibilities and limitations of immersive VR environments.